Mitochondrial DNA haplotyping revealed the presence of mixed up benign and neoplastic tissue sections from two individuals on the same prostatic biopsy slide. Issue 1 (27th December 2004) - Alonso, A; Alves, C; Suárez-Mier, M P; Albarrán, C; Pereira, L; Fernández de Simón, L; Martín, P; García, O; Gusmão, L; Sancho, M; Amorim, A
Abstract : DNA typing was requested to investigate a presumptive cancer diagnosis error by confirming whether benign and cancerous prostatic tissue in the same presurgical haematoxylin and eosin stained slide belonged to the same person. After independent histological re-examination of the slide by a pathologist, manual slide dissection was used to guarantee independent and high recovery DNA isolation from each tissue section, avoiding carryover and background contamination. Nuclear DNA quantification performed by real time polymerase chain reaction (PCR) revealed the absence of human DNA for short tandem repeat (STR) typing. Mitochondrial DNA was only obtained by performing PCR of very short fragments (∼100 bp), indicating high DNA degradation. Different low frequency hypervariable region I haplotypes were obtained from each tissue section (normal tissue section haplotype: 16224C, 16234T, 16311C, 16356C; cancer tissue section haplotype: 16256T, 16270T, 16293G). Only the normal tissue section haplotype matched that obtained from the patient's blood sample, indicating that the cancer tissue section originated from an unknown patient. These results supported the hypothesis of sample mix up during block processing or slide preparation by a carryover mechanism. Mitochondrial genetic typing is recommended to exclude the possibility of carryover artefacts when low DNA content and high degradation compromise conventional STR typing.